The Effect of CBR of Soil Stabilised with Polyacrylamide on Flexural Pavement Thickness Based on SKBI 1987 - Yullianty Noorlaelasari; Ery Radya Juarti; Agus Suyono; Linda Aisyah; Salma Oktavania; Anissa Puspa Nugraha; Suliman Badawi Ahmed (Potensi: Jurnal Sipil Politeknik, 2024)
Roads must have safety and comfort, which can be seen through the condition of the pavement. A good pavement is influenced by a good bearing capacity of the subgrade. Not infrequently, road damage that occurs is caused by a lack of bearing capacity of the subgrade (CBR<6). One way to improve the bearing capacity of the subgrade is to stabilize it with polyacrylamide (PAM) synthetic polymer. Subgrade stabilization was carried out on local soil at Jalan Cisasawi, Desa Cihanjuang with a percentage of 4%, 6%, 8%, 10%, and 12% of the dry soil weight. From the results of laboratory CBR testing, calculations were made to determine the effect on the thickness of flexible pavement using the SKBI 1987 method. After the calculation, it can be concluded that the CBR value affects the thickness of the flexible pavement layer. The greater the subgrade CBR value, the thinner the pavement thickness (with 8% polyacrylamide). This has been proven in the calculation where PAM managed to increase the bearing capacity of the soil to the maximum at 8% PAM content (soaked CBR 16.4% and unsoaked CBR 20.5%) and the thickness of the lower foundation layer is 25 cm (the thinnest among other levels).